A responsive design approach for supporting mobile access to virtual and remote laboratories - Zervas, P.; Trichos, A.; Sampson, Demetrios; Li, N. (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. Remote and virtual laboratories aim to overcome typical constraints of traditional laboratories and offer access to laboratory experiments without location and time restrictions. Additionally, the continuous growth of mobile devices' ownership, as well as their increased technical capabilities, have created an emerging trend for supporting mobile access to virtual and remote labs. Existing approaches in this direction are focusing on developing device-dependent mobile apps for accessing the experiment(s) of the original remote or virtual lab. This creates difficulties related to (a) seamless access to experiments of remote or virtual labs across various mobile devices and (b) additional costs that are needed for developing different versions of the same mobile app that meets the specific technical requirements of each mobile device. In this paper, we aim to address this issue by adopting a responsive design approach for developing mobile web apps towards providing seamless access through various mobile devices to existing virtual and remote labs.